A new generation of Bt maize for control of fall armyworm (Spodoptera frugiperda). Issue 8 (1st April 2021) - Horikoshi, Renato J; Vertuan, Hallison; de Castro, Ancidériton A; Morrell, Kimberly; Griffith, Cara; Evans, Adam; Tan, Jianguo; Asiimwe, Peter; Anderson, Heather; José, Márcia O M A; Dourado, Patrick M; Berger, Geraldo; et al.
Abstract: BACKGROUND: The pyramided genetically modified maize ( Zea mays [L.]) event MON 95379, expressing the Cry1B.868 and Cry1Da_7 proteins, was designed to protect against larval feeding damage by the fall armyworm, Spodoptera frugiperda (FAW). Here, we conducted laboratory, greenhouse, and field studies to assess the dose and field efficacy of MON 95379 against FAW and inform the development of insect resistance management plans. RESULTS: The Cry1B.868 and Cry1Da_7 proteins were active against susceptible FAW neonates in diet‐incorporation bioassays: median lethal concentration [LC50 ] (95% CI) = 62.8 (42.6–87.6) μg/ml diet for Cry1B.868 and 9.4 (5.3–18.6) μg/ml diet for Cry1Da_7. In laboratory leaf disc bioassays, MON 95379 maize and experimental maize lines expressing the individual components were effective in controlling susceptible FAW. In whole‐plant assays, MON 95379 controlled FAW resistant to the Cry1A.105 and Cry2Ab2 proteins. Likewise, under field conditions, MON 95379 maize expressing Cry1B.868 and Cry1Da_7 was highly effective at protecting plants against the larval feeding of FAW. CONCLUSIONS: The expression of Cry1B.868 and Cry1Da_7 in MON 95379 consistently protected maize plants against larval feeding by FAW and represents an alternative to manage trait resistance issues in South America. © 2021 Bayer Crop Science‐US. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : The pyramided genetically modified maize ( Zea mays [L.]) event MON 95379, expressing the Cry1B.868 and Cry1Da_7 proteins was designed to protect against larval feeding damage of the fall armyworm, Spodoptera frugiperda (FAW). The expression of Cry1B.868 and Cry1Da_7 in MON 95379 consistently protected maize plants against larval feeding of FAW and represents an alternative to manage trait resistance issues in South America.